Mapping the trends and impact of research collaboration between countries in oral implantology publications: A bibliometric analysis from 1999 to 2019 - Dini, Caroline; Pereira, Marta Maria Alves [UNESP]; Souza, João Gabriel Silva; de Avila, Erica Dorigatti [UNESP]; Barão, Valentim Adelino R. (Elsevier, 2022)
Statement of problem: Scientific collaboration provides a suitable strategy for enhancing the exchange of knowledge and technological development. However, the impact of collaboration in oral implantology research between countries and how it has been influenced by the income status of the country has not been previously evaluated. Purpose: The purpose of this bibliometric analysis was to evaluate how collaboration between countries affected oral implant publications and whether patterns of collaboration differ depending on the country's income. Material and methods: Articles were retrieved from 7 well-established journals whose scope included oral implantology at 5 time points (1999, 2004, 2009, 2014, and 2019). Data were extracted, and descriptive, bivariate, and multivariate logistic regression analyses were performed (α=.05). Results: A total of 1944 articles were included; of which, 27.5% presented collaboration between countries. In 2009, 2014, and 2019, collaboration between countries was more likely to occur than at previous time points (P≤.005). Corresponding authors with a higher h-index (P<.05) and authors from Europe and North America (P<.001) were more likely to establish international connections. The possibility of collaboration between countries was higher for animal studies (P<.001) and for articles published by Clinical Oral Implants Research (P=.026). Collaborations between high-income and upper-middle– or lower-middle–income countries were more likely to happen in 2014 and 2019 (P<.05), as well as when the number of authors was higher (P=.015), compared with collaboration between high-income countries. With regard to the continent, European articles were less likely to have collaborations with upper-middle– or lower-middle–income countries (P<.001). Conclusions: The findings revealed that some parameters related to the study, authors, countries, and journals were statistically associated with the presence of collaboration between countries. However, the bibliometric parameters showed different trends when countries of different incomes established collaboration.